Transformasi pustakawan dalam meningkatkan kemampuan mahasiswa terhadap penelusuran informasi di dunia maya - Fitriyani, Fitriyani; Zulfa, Siti Ukhtiya; Miswan, Miswan (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2023)
Purpose. College libraries are no longer just waiting for users to come to visit and serve book return loans, but a new breakthrough is needed to seduce students. One of them is that librarians can act as educators. Librarians can provide education to users in accessing, searching, and using information sources effectively. This article discusses the role of librarians in digital information tracing training at UIN Walisongo Library.Methodology. The research method used is quantitative with a descriptive approach, which allows for a more detailed investigation of the stages taken by librarians in providing this training.Result and discussion. There are several stages carried out by librarians in providing digital information tracing training, namely the introduction of information sources, information tracing tools, search strategies, and citation management. Through this training, librarians guide students in understanding and mastering these steps, enabling them to access, search for, and use information more competently in an academic and research context. Conclusion. Reveal several stages undertaken by librarians in providing digital information tracing training, covering source introduction, tracking tool utilization, search strategy formulation, and citation management guidance. The pivotal role of librarians involves guiding students to understand and master stages of information retrieval. This transforms librarians into proactive educators, exceeding traditional roles. By transferring essential digital information tracing skills, librarians contribute to students' academic success, emphasizing their crucial role in shaping information-literate individuals.